Contribution of non‐native plants to the phylogenetic homogenization of U.S. yard floras. Issue 3 (12th March 2019) - Padullés Cubino, Josep; Cavender‐Bares, Jeannine; Hobbie, Sarah E.; Hall, Sharon J.; Trammell, Tara L. E.; Neill, Christopher; Avolio, Meghan L.; Darling, Lindsay E.; Groffman, Peter M.
Abstract: Cultivation and spread of non‐native plant species may result in either phylogenetic homogenization (increasing similarity) or differentiation (decreasing similarity) of urban floras. However, it is unknown how non‐native species influence homogenization of cultivated versus spontaneously occurring species in cities, and which traits are associated with species that promote homogenization versus differentiation. In this study, we compared homogenization effects of cultivated and spontaneous non‐native species in yard floras across and within seven widely distributed U.S. cities. Additionally, we explored which traits explained their particular contribution to homogenization. We recorded plant presence/absence in 178 private yards distributed among seven metropolitan statistical areas in the United States. We compared phylogenetic homogenization effects of non‐native species within both the cultivated and spontaneous species pools using phylogenetic dissimilarities and the homogenization index. Then, we expressed contributions of non‐native species to the homogenization of each pool as a function of two different sets of plant functional traits using phylogenetic generalized least square (PGLS) models across and within cities. Across cities, spontaneous non‐native species homogenized, and cultivated non‐native species differentiated, yard floras. Within the spontaneous pool, short, small‐seeded non‐native plants and non‐native grasses significantly homogenized yard floras. Within the cultivated pool, species contribution to homogenization was best predicted by plant height, presence of showy flowers, and growth form, with non‐native grasses significantly homogenizing cultivated yard floras. Within cities, non‐native species—whether they were cultivated or spontaneous—consistently homogenized yard floras of the three northern cities and differentiated yard floras of three of the four southern cities, suggesting that homogenization processes are context‐ and scale‐dependent. Likewise, traits explaining homogenization differed substantially among cities. The inconsistent patterns among cities in the plant traits that promoted homogenization of both cultivated and spontaneous species suggest that local environmental and anthropogenic conditions of individual cities imposed strong constraints on trait selection. Linking plant functional traits that promote homogenization with residents' preferences for vegetation may further enhance understanding of how yard plant communities assemble at regional and local scales.